Stereoselective Rhodium-Catalyzed Isomerization of Stereoisomeric Mixtures of Arylalkenes - Yang, Hongxuan; Dong, Wenke; Wang, Wencan; Li, Tao; Zhao, Wanxiang (Synthesis, 2020)
A new efficient method for the synthesis of a high ratio of E-alkenes from E/Z mixtures of alkenes with B2pin2 in the presence of a rhodium catalyst is described. This reaction features mild reaction conditions, broad functional group tolerance, and highly great application potential.
Keywords: isomerization; stereoselectivity; rhodium; alkene; interconversion